Antioxidants Effectivity In Skin Lotion Formulation Of Mesocarp Fruit Extract Lontar (Borassus Flabellifer) Against White Rats Wistar Male In-Situ - Luthfiasari Amatullah; Tri Nur Cahyaningrum; Anisa Nur Fidyaningsih (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2017)
Study of bioactive mesocarp on palm fruits has been conducted previously. Therefore, this research aims to make a preparation of antioxidant skin lotion palm fruit mesocarp (Borrasus flabellifer) and to evaluate the effects of antioxidants on skin preparation lotion palm fruit (Borrasus flabellifer) by In-situ.This study was an experimental study by making a preparation of skin lotion on the stability of the corresponding and testing the antioxidant treatment with a sample of 30 rats male wistar strain. The antioxidant test was divided into 5 groups randomly: negative control (-), positive control (compound sunscreen brands parasol SPF 33), group 1 (lotio extract palm fruit mesocarp with a concentration of 0.2%), group 2 (lotio palm fruit mesocarp extract with concentration of 0.4%) and group 3 (lotio palm fruit mesocarp extract with concentration 0.8%).The results of in-situ states showed 0.8% extract of palm fruit mesocarp exhibited the least erythema score which was an average of 1.7. It was comparable to positive control which exhibited similar erythema score.